Monitoring of air pollution with heavy metals in the vicinity of a ferronickel smelter plant by deposited dust - Bačeva, Katerina; Stafilov, Trajče; Šajn, Robert (Macedonian Journal of Ecology and Environment, 2012)
Comprehensive monitoring was applied to assess environmental pollution in the vicinity of a ferronickel smelter plant in Kavadarci (Republic of Macedonia) and its environs. The total dust deposition is a very useful method to follow the increased presence of some chemical elements in the atmosphere as a result of anthropogenic activities. The data from such surveys allow for assessing both spatial and temporal trends in heavy metal deposition and an examination of the areas with higher deposition of heavy metals. In order to determine the daily amounts of fine dust contained in the air, samples of total deposited matter (deposited dust) were collected at three locations in the area. The total quantity of deposited dust was monitored monthly for a period of one year. In total 18 elements (Al, As, Ca, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, Pb, Sr, V, Zn) were determined by two complementary analytical techniques: atomic emission spectrometry with inductively coupled plasma (AES-ICP) and electrotermal atomic absorption spectrometry (ETAAS). Based on the comparison of distribution patterns of elements determined in attic and deposited dust, one anthropogenic geohemical association (Co-Cr-Fe-Ni) was detected in the investigated region which is a result of the activities of a ferronickel metallurgical plant.